Rogue Warrior: The Real Team - Marcinko, Richard (Simon & Schuster Inc., 1999)
The retired naval commander chronicles the real-life exploits of the Navy SEALs who inspired the characters in his best-selling Rogue Warrior series, profiling the members of his team, their training, their combat missions, and the characteristics that made them successful warriors.
Keywords: Biography and Autobiography; Non-Fiction